Cenozoic evolution of the Yangjiang-Yitong’ansha fault zone in the northern South China Sea: Evidence from 3D seismic data - Zhan, Huawang; Wang, Guangzeng; Peng, Guangrong; Suo, Yanhui; Wang, Pengcheng; Du, Xiaodong; Zhou, Jie; Li, Sanzhong; Zhu, Dingwei (Frontiers in Earth Science, 2023)
The Yanjiang-Yitong’ansha Fault Zone (YYFZ) traverses the Pearl River Mouth Basin (PRMB) and plays an essential role in basin formation and hydrocarbon accumulation in the PRMB. Because of the lack of seismic data, its distribution, evolution, and effect on the basin evolution in the Cenozoic are poorly known. Based on a detailed interpretation of 3D multi-channel seismic data and previous research results, the YYFZ was identified and characterized. It comprises a series of NW-trending strike-slip faults that exhibit horsetail and en echelon structures in the map view and flower-like or Y-shaped structures in the profile view. By comprehensively analyzing the Paleogene migration of depocenters, activity characteristics of the YYFZ-related faults, and the relationships between faults and sedimentary sequences along the YYFZ, we propose the sinistral motion of the YYFZ initiated at about 35Ma. The YYFZ served as a transfer zone during the intense rifting in the PRMB from 65 to 35 Ma. Then due to the combined effect of the Indian-Eurasian collision to the west, the Pacific subduction to the east, and the proto-SCS slab-pull to the south, it became a sinistral transtensional fault from 35 Ma to 16.5 Ma. Our results highlight the significant role of the NW-trending fault systems in the basin formation and the regional tectonic evolution of the PRMB.